Quiz. Correct answer to the quiz. check your diagnosis Primary carcinoid tumour in horseshoe kidney - Litwinowicz, Radosław; Szpor, Joanna; Januś, Grzegorz; Worek, Marek; Okoń, Krzysztof (Polish Journal of Pathology, 2011)
Primary renal carcinoid tumours are extremely rare. To date, approximately 60 cases have been reported, mostly as case reports with only few series noted. The pathogenesis of this tumour is uncertain because neuroendocrine cells are not found in normal adult renal parenchyma. We report a case of primary renal carcinoid occurring in a horseshoe kidney in a 66-year-old patient. A clinical, histological and immunohistochemical picture of this tumour is presented.